2021
DOI: 10.1155/2021/5848525
|View full text |Cite
|
Sign up to set email alerts
|

CALL-Enhanced L2 Vocabulary Learning: Using Spaced Exposure through CALL to Enhance L2 Vocabulary Retention

Abstract: CALL- and MALL-enhanced learning applications have dominated the field of second language (L2) learning recently. This study aims to investigate the effect of applying a CALL-enhanced L2 vocabulary learning software program on the L2 vocabulary development of English as Foreign Language (EFL) students. 76 preintermediate EFL students registered at a foreign language school were chosen from a total of 156 students after running an Oxford Quick Placement Test (OQPT). The participants were randomly assigned to tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 38 publications
0
19
0
1
Order By: Relevance
“…CALL has been developed into a wide range of applications and language teaching and learning approaches, beginning with the drill-andpractice based programs to the virtual learning environments and mobileassisted language learning (MALL) (Shokrpour et al, 2019). CALL as a technology-mediated language learning tool has shown potential for L2 learning outcomes (Boulton & Cobb, 2017;Lin, 2015;Milton et al, 2012), including vocabulary development (Çakmak et al, 2021(Çakmak et al, , Kayaaltı, 2018.…”
Section: Computer-assisted Language Learning (Call)mentioning
confidence: 99%
See 2 more Smart Citations
“…CALL has been developed into a wide range of applications and language teaching and learning approaches, beginning with the drill-andpractice based programs to the virtual learning environments and mobileassisted language learning (MALL) (Shokrpour et al, 2019). CALL as a technology-mediated language learning tool has shown potential for L2 learning outcomes (Boulton & Cobb, 2017;Lin, 2015;Milton et al, 2012), including vocabulary development (Çakmak et al, 2021(Çakmak et al, , Kayaaltı, 2018.…”
Section: Computer-assisted Language Learning (Call)mentioning
confidence: 99%
“…A study by Son (2001) showed no different effects of electronic glossaries on vocabulary learning and reading comprehension because "the computer-based assistance for delivering the meanings of words in each study was accompanied by different presentation methods" (p.33). Despite these arguments, it is worth noting that applying CALL based on the students' actual needs can optimize the students' motivation in learning English (Çakmak et al, 2021;Shokrpour et al, 2019). Furthermore, the role of technology and its impact on learning differ depending on the population (Plonsky & Ziegler, 2016).…”
Section: Computer-assisted Language Learning (Call)mentioning
confidence: 99%
See 1 more Smart Citation
“…Different colleges, including regular and e-learning or distance learning, provide several forms of education. E-learning is playing a key role in shaping the modern society in which the whole world depends on the Internet (Almazova, et al, 2016;Alotaibi & Kumar, 2019;Çakmak, Namaziandost, & Kumar, 2021;Kumar et al, 2021). E-learning programmes allow students to adopt and promote selforientation and autonomous approaches to learning.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers nowadays have a prominent interest in vocabulary knowledge. Therefore, literature shows that some of them link this topic to the four skills of the language learning, listening, reading, writing, and speaking, and some of them link the topic to other linguistic aspects (Luo, Wan, & Zhang, 2021;Namaziandost, Kumar, & Çakmak, 2021;Wero, Machmud, & Husain, 2021;Kalay, 2021;Ha, 2021;Enayat & Derakhshan, 2021).…”
Section: Introductionmentioning
confidence: 99%